Predictive Validity of the Intensive Course to Language Skills - B. Budiyono (Magister Scientiae, 2011)
Through the coefficient of correlation, we can measure the degree or extent of the correlation between two variables. On the basis of the coefficient of correlation we can also determine whether the correlation is positive or negative and also its degree or extent. In order to prove the existence of correlation between IC to language skill courses, the correlation coefficient was examined by the Pearson product at the significant level of. 05. the computation of the predictive validity of IC to the listening course is 0,8837459 (high and positive) ; the computation of the predictive validity of IC to speaking is 0,73469 (moderate and significant).The computation of the predictive validity of IC to reading is 0,60041( moderate and significant); the computation of the predictive validity of IC to writing is 0,70172( moderate, significant). The coefficient of the IC to listening is high; the others are moderate